2015
DOI: 10.5194/hessd-12-4413-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative historical hydrology in Europe

Abstract: Abstract. In the last decades, the quantification of flood hydrological characteristics (peak discharge, hydrograph shape, and runoff volume) from documentary evidence has gained scientific recognition as a method to lengthen flood records of rare and extreme events. This paper describes the methodological evolution of the quantitative historical hydrology under the influence of developments in hydraulics and statistics. In the 19th century, discharge calculations based on flood marks was the only source of hy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 118 publications
2
19
0
1
Order By: Relevance
“…In the Mediterranean region, there is a smaller increase, or even decrease in more recent decades, of extreme precipitation than in other parts of Europe which is also consistent with trends in number of events in the two sub-domains. The overall upward trend and the contrast between northern and southern Europe is consistent with other studies, both for extreme precipitation 13 , 58 , 59 and large flood occurrences 15 , 16 . However, the number of events and flooded area must have had less pronounced trends for the continent as a whole, since the records of past floods have grown more complete over time, as shown in Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the Mediterranean region, there is a smaller increase, or even decrease in more recent decades, of extreme precipitation than in other parts of Europe which is also consistent with trends in number of events in the two sub-domains. The overall upward trend and the contrast between northern and southern Europe is consistent with other studies, both for extreme precipitation 13 , 58 , 59 and large flood occurrences 15 , 16 . However, the number of events and flooded area must have had less pronounced trends for the continent as a whole, since the records of past floods have grown more complete over time, as shown in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Qualitative and quantitative hydrological studies for Europe have indicated no general continental-wide trend in river flood occurrences, extreme precipitation, or annual maxima of runoff 12 14 . However, substantial variations between different catchments have been observed, ranging from an increase in north-western Europe to no trend or a decrease in other parts of the continent 15 , 16 . Similar findings were reported for storminess along the European coasts 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Historical flood information and paleoflood records can supplement systematic gauge records to improve at‐site FFA, but unlike gauge records, they are noncontinuous and are typically described in terms of above, or below, a flood threshold [ Swain et al ., ]. Historical flood information, which can be derived from flood marks on old buildings, newspaper reports, and oral descriptions [ Herget and Meurs , ], is well documented in Europe with records dating back to A.D. 1500 [ Brázdil et al ., ] and is now being incorporated into FFA [e.g., Benito et al ., ; Machado et al ., ]. However, in localities where European settlement occurred relatively recently, such as in Australia, historical flood information has limited capacity to extend the analysis period for FFA.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the documents, the information available may include the origins, scale, and impacts of a flood (Brázdil et al, ). Often accounts in different documents will contradict each other making cross‐referencing of various sources a necessity (Benito, Brázdil, Herget, & Machado, ; Brázdil, Kundzewicz, & Benito, ).…”
Section: Background To the Use Of Historical Interval Censored Data Imentioning
confidence: 99%